1994
DOI: 10.1677/joe.0.1420077
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of rat thyroxine-binding globulin and transthyretin: studies in thyroidectomized and hypophysectomized rats given tri-iodothyronine or/and growth hormone

Abstract: We have investigated the role of the thyroid compared with the hypophysis in the regulation of the two saturable thyroid hormone carriers of rat serum, thyroxine-binding globulin (TBG) and transthyretin (TTR). We examined, at serum and hepatic mRNA level, the responses of TBG and TTR to thyroidectomy (Tx), hypophysectomy (Hx) and replacement treatments with tri-iodothyronine (T3) or/and GH, both hormones which are depleted when the thyroid or hypophysis are removed. The studies were performed on male rats at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 0 publications
2
18
0
Order By: Relevance
“…In rat experiments, thyroidectomy induced TBG reexpression which was completely reversed by T3 replacement and unresponsive to GH replacement, indicating a direct negative control by thyroid hormones [24]. The concomitant decrease of TBG and thyroid hormones in the Ox group indicates that the TBG downregulation was not mediated by the thyroid hormones.…”
Section: Visitmentioning
confidence: 88%
See 1 more Smart Citation
“…In rat experiments, thyroidectomy induced TBG reexpression which was completely reversed by T3 replacement and unresponsive to GH replacement, indicating a direct negative control by thyroid hormones [24]. The concomitant decrease of TBG and thyroid hormones in the Ox group indicates that the TBG downregulation was not mediated by the thyroid hormones.…”
Section: Visitmentioning
confidence: 88%
“…Hypophysectomy induced also TBG reexpression which was less effectively antagonized by T3. The authors hypothesized that there is an alternative pathway for TBG regulation, independent of the thyroid, but involving GH possibly for its role in the control of carbohydrate metabolism [24]. Davidson described an anti-insulinic effect of hypophysectomy [21].…”
Section: Visitmentioning
confidence: 99%
“…Collectively, these three proteins transport more than 95% of T 3 and T 4 hormones (Barlow, 1997;Bartalena and Robbins, 1992). In rats, a significant difference is that TBG is not found between 2 and 7 months, the age range typically used in basic toxicology studies (Vranckx et al, 1994). In adult rats, T 4 and T 3 are bound to the low affinity carriers albumin and TTR.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in urinary excretion of T 4 and deiodination of T 4 to rT 3 following Tx warrant further investigation. In addition to these changes in T 4 metabolism, Vranckx et al (1994) reported that Tx induces expression of T 4 -binding globulin (TBG), and suggested that regulation of TBG may thus be important for thyroid hormone homeostasis. Further study is required to completely determine the mechanisms of thyroid hormone homeostasis after Tx.…”
Section: Discussionmentioning
confidence: 99%